1999
DOI: 10.1093/oxfordjournals.jbchem.a022258
|View full text |Cite
|
Sign up to set email alerts
|

An Azide-Insensitive Superoxide Dismutase from a Hyperthermophilic Archaeon, Sulfolobus solfataricus

Abstract: The superoxide dismutase (SOD) gene of Sulfolobus solfataricus, a hyperthermophilic archaeon, was cloned and expressed in Escherichia coli, and its gene product was characterized. When the protein was expressed in E. coli, it formed a homodimer that contained both Mn and Fe. Metal reconstitution experiments of the SOD with Fe or Mn showed that only the Fe-reconstituted SOD was active. Substitution of Tyr88 to Phe did not affect the metal specificity of the enzyme. The Fe-reconstituted SOD was extremely resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Both enzymes displayed relatively strong resistance against azide (Mnand Fe-SOD activity decreased 50% with 380 and 340 mM azide, respectively). This resistance against azide has also been observed in other archaeal SODs (44,45).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Both enzymes displayed relatively strong resistance against azide (Mnand Fe-SOD activity decreased 50% with 380 and 340 mM azide, respectively). This resistance against azide has also been observed in other archaeal SODs (44,45).…”
Section: Resultssupporting
confidence: 72%
“…Mn-and Fe-SODs are closely related in amino acid sequence and three-dimensional structure. Among (hyper)thermophilic archaea, Fe-SODs have been reported from Sulfolobus solfataricus (11,44), Sulfolobus acidocaldarius (18), Acidianus ambivalens (17), and Thermoplasma acidophilum (37). Although Mn-and Fe-SODs generally exhibit a strict metal specificity for SOD activity (34), several cambialistic SODs, which are active with either Mn or Fe, have been reported.…”
mentioning
confidence: 99%
“…Superoxide dismutase from M. barkeri was inhibited by azide and H 2 O 2 but to a lessr extent than the iron superoxide dismutase from E. coli (Sigma), which we used as control (Table 2). A relative insensitivity to azide and H 2 O 2 has also been reported for the iron superoxide dismutases from Methanobacterium thermoautotrophicum and Sulfolobus solfataricus (Takao et al 1991;Yamano and Maruyama 1999). Superoxide dismutase from M. barkeri was not inhibited by 10 mM cyanide, which is a property shared among all iron and manganese superoxide dismutases.…”
Section: Resultsmentioning
confidence: 55%
“…Although a few exceptions have been reported [17,18], these three differences could be the primary candidates to account for the metal specificity of the Fe-and Mn-SOD activity [19], improving on the suggestions by Parker and Blake [20] and Yamakura et al [21]. Recently, Yamano and Maruyama [22] reported that the substitution of Tyr-77 by Phe in the metal-specific Fe-SOD from Sulfolobus solfataricus did not change the metal-specific activity of the enzyme. Therefore, the third difference may not contribute to the metal-specific activity of Fe-and Mn-SODs.…”
Section: Introductionmentioning
confidence: 81%